PENGARUH KAPASITAS SUMBER DAYA MANUSIA, PEMANFAATAN TEKNOLOGI INFORMASI, PENGAWASAN KEUANGAN DAERAH DAN PENGENDALIAN INTERN TERHADAP KETERANDALAN DAN KETEPAT WAKTUAN PELAPORAN KEUANGAN DI SATUAN KERJA PERANGKAT KOTA BANDA ACEH - nurdiansyah, rizki; Nadirsyah, Nadirsyah (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2018)
This purpose of the research is to examine the effect capacity of human resource, the use of information technology, financial supervision , and internal control of the reliability and timeliness of financial statement. This is study used based on purposive methode, sample of 80 employees in the work unit of Banda Aceh. The research type used is hypothesis testing reseearch. The sata waas collected by using questionnaire. The questionnaire were delivered to every employees as sample. The analytical method used is multiple regression analysis with SPSS version 23. The results indicate that capacity of human resource, the use of information technology, financial supervision , and internal control simultaniously of the reliability and timeliness of financial statement. Partially, human resource capacity, the use of information technology, financial supervision , and internal controls of the reliability and timeliness of financial statement